Comparative hemolymph proteomic analyses of the freezing and resistance-freezing Ostrinia furnacalis (Guenée) - Zhu-Ting Zhang; Huan Wang; Hui Dong; Bin Cong (Scientific Reports, 2024)
Abstract The Asian corn borer, Ostrinia furnacalis (Guenée) (Lepidoptera: Crambidae), is one of the most harmful pests of maize in Asia. It poses a significant threat to maize production, causing economic losses due to its strong ecological adaptation. In this study, we compared and analyzed the hemolymph proteome between freezing and resistance-freezing O. furnacalis strains using two-dimensional gel electrophoresis to gain insights into the mechanisms of cold resistance. The results revealed that 300–400 hemolymph protein spots were common, with 24 spots showing differences between the two strains. Spectrometry analysis revealed 21 protein spots, including 17 upregulated spots and 4 downregulated ones. The expression of upregulation/downregulation proteins plays a crucial role in the metabolism, energy supply, and defense reaction of insects. Proteomics research not only provides a method for investigating protein expression patterns but also identifies numerous attractive candidates for further exploration.